2016
DOI: 10.3389/fpls.2016.00981
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Nutrition Improves the Potential of Wheat (Triticum aestivum L.) to Alleviate the Effects of Drought Stress during Vegetative Growth Periods

Abstract: Efficient nitrogen (N) nutrition has the potential to alleviate drought stress in crops by maintaining metabolic activities even at low tissue water potential. This study was aimed to understand the potential of N to minimize the effects of drought stress applied/occur during tillering (Feekes stage 2) and jointing (Feekes stage 6) growth stages of wheat by observing the regulations and limitations of physiological activities, crop growth rate during drought periods as well as final grain yields at maturity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
94
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 41 publications
10
94
0
3
Order By: Relevance
“…Gyuga et al [48] reported that N greatly influences photosynthetic processes, and deficiency of N leads to the declined photosynthesis. Similarly, Abid et al [49] in their findings concluded that management of N nutrition could build drought tolerance in wheat by maintaining higher photosynthetic activities and antioxidative defense system during vegetative growth periods. A primary driving force for dry matter production in photosynthesis; thus, its management through the optimization of N could help to improve dry matter production in the plant.…”
Section: Discussionmentioning
confidence: 89%
“…Gyuga et al [48] reported that N greatly influences photosynthetic processes, and deficiency of N leads to the declined photosynthesis. Similarly, Abid et al [49] in their findings concluded that management of N nutrition could build drought tolerance in wheat by maintaining higher photosynthetic activities and antioxidative defense system during vegetative growth periods. A primary driving force for dry matter production in photosynthesis; thus, its management through the optimization of N could help to improve dry matter production in the plant.…”
Section: Discussionmentioning
confidence: 89%
“…Also, accumulation of ions promotes turgor maintenance, which contributes to increased absorption of water in water‐stressed plants and thereby results in improving drought resistance ( da Silva et al., ). Furthermore, N being an important component of chlorophyll and Rubisco affects the metabolism of the plant under drought stress ( Abid et al., ). Functional activity of the photosynthetic apparatus of leaf largely depends on the availability of N in plants ( Brennan , ).…”
Section: Discussionmentioning
confidence: 99%
“…Pervious study demonstrated that photosynthetic rate under drought stress is closely related to the chlorophyll and N contents of the leaf (Park and Lee 2003). Previous studies have also reported that low N is the major constraint to wheat yield under drought stress (Madani et al 2010;Abid et al 2016). Nawaz et al (2012) reported that early and late drought stress significantly decreases the N uptake by the wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen nutrition has been elucidated to mitigate drought stress in crops. Nitrogen nutrition maintains metabolic activities of plant even at low tissue water potential (Zlatev and Lidon 2012;Abid et al 2016). Pervious study demonstrated that photosynthetic rate under drought stress is closely related to the chlorophyll and N contents of the leaf (Park and Lee 2003).…”
Section: Discussionmentioning
confidence: 99%